Proteolysis of splicing factors during rat and monkey cell fractionation. - La Branche, H (1991)
We have investigated the ability of various rat and monkey cell lines to yield nuclear extracts that would allow splicing of a model adenovirus pre-mRNA substrate. Extracts from normal FR3T3, rat-1 and CV-1 fibroblasts were unable to assemble splicing complexes and displayed a dramatic reduction in the binding activity of the splicing factor 65 kD U2AF. These results correlated with reduced levels of 65 kD U2AF and the snRNP-associated B protein. When a battery of protease inhibitors was used during cell fractionation, increased levels of 65 kD U2AF and B proteins were detected. Most importantly, U2AF binding and complex formation were dramatically improved in FR3T3, rat-1 and CV-1 extracts. Interestingly, transformation of rat and monkey cells with the SV40 large T antigen yielded extracts active in complex formation. Similar extracts were generated following transformation of rat-1 cells with the Py middle T antigen but not with the v-fos oncogene. Only SV40-transformed FR3T3 extracts displayed splicing activity. Our results indicate that proteolysis is a major obstacle encountered during the preparation of active extracts from normal rat and monkey cells and suggest that cells transformed with T antigens manifest reduced proteolysis during fractionation.